ANTIRADICAL, ANTIBACTERIAL AND ANTIFUNGAL ACTIVITY OF HARPULLIA ARBOREA (BLANCO) RADLK. (SAPINDACEAE) - L., Raghavendra H.; R., Prashith Kekuda T.; N., Karthik K.; N., Ankith G. (International Journal of Current Pharmaceutical Research, 2017)
Objective: The present study was conducted to investigate antiradical and antimicrobial potential of extract of Harpullia arborea (Blanco) Radlk. (Sapindaceae) leaves obtained by maceration process. Methods: Antiradical activity of leaf extract was performed by DPPH and ABTS radical scavenging assays. Antibacterial activity of leaf extract was carried out by Agar well diffusion assay. Antifungal activity of leaf extract was carried out by Poisoned food technique. Results: Leaf extract displayed concentration dependent scavenging of radicals with potent scavenging activity against ABTS radicals (IC50 value 4.26Âµg/ml) when compared to DPPH radicals (IC50 value 27.26Âµg/ml). Extract exhibited inhibitory activity against all test bacteria. Marked and least activity was observed against Staphylococcus epidermidis and Escherichia coli respectively. Considerable reduction in the mycelial growth of test fungi was observed in poisoned plates. Curvularia sp. and Alternaria sp. were inhibited to highest and least extent respectively. Conclusion: In suitable form, the plant can be used to treat oxidative damage, infectious diseases caused by pathogenic bacteria and to manage seed-borne fungi.